Developing an evidence and theory based intervention that seeks to promote positive adolescent health and education outcomes. (November 2018) - Pringle, Jan; Doi, Lawrence; Jepson, Ruth; McAteer, John
Abstract: Background: As they mature physically, adolescents become increasingly autonomous in decision making, yet may still lack the experience and knowledge necessary to always make well-informed choices. This can present challenges to their health and wellbeing. A trusted adult can provide crucial support during this developmental stage. The aim of this study was to demonstrate how the six steps in quality intervention development framework (6SQuID) can be used, with research or review findings, to inform the development of adolescent interventions that promote positive outcomes. Methods: Using the synthesised findings from two systematic reviews on adolescents, one involving physiological changes during adolescence, the other the role of trusted adults for adolescents, we sought to illustrate how interventions might be designed to impact positively upon adolescent health or educational outcomes (e.g. physical activity, sexual behaviour, substance use, sleep, eating behaviour, educational engagement). Both reviews followed PRISMA guidelines. We applied the 6SQuID framework to the findings from the reviews, and used the sequential steps within 6SQuID to build a proposed evidence-based intervention, incorporating social learning theory to identify how change could be influenced. Findings: The example intervention, a training session for teaching assistants, aimed to improve confidence in dealing with adolescents through increased understanding of adolescent physiological development, and the role that trusted adults can play in their lives. Teaching assistants may be crucial to support pupils (as trusted adults) especially in challenging situations. Specific training on adolescent development may especially benefit those new to the role. The intervention details key issues in adolescent development, behaviour-influencing factors, why, when, and what type of support might be needed, identification of those who might need more support (eg, at risk groups), confidentiality considerations, and when to involve other staff or agencies. Interpretation: The example intervention illustrates how the 6SQuID framework can be used for intervention development, using specific research (systematic review) findings, to promote adolescent wellbeing. The example details how to operationalise 6SQuID in practical terms that are transferrable to other populations and situations. This illustrative case may be of use to inform the design, development, and implementation of a variety of alternative interventions. Funding: Medical Research Council (MR/KO 023209/1), Chief Scientist Office, and NHS Health Scotland.